2005
DOI: 10.1300/j070v14n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Childhood Sexual Abuse Experience Between Adult Hispanic and Anglo Women in a Primary Care Setting

Abstract: The literature on racial and ethnic factors in childhood sexual abuse is limited. The purpose of this exploratory study was to document Hispanic-Anglo differences in childhood sexual abuse experiences and assess whether these differences may be explained by socio-demographic and family environmental differences. Adult Hispanic (n = 69) and Anglo (n = 19) women from a family medicine clinic waiting room reporting a history of childhood sexual abuse completed an in-depth survey concerning the sexual abuse experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…It is consistently reported in the literature that compared to other ethnic groups, Latina women and girls are more likely to be abused by male family members or relatives such as uncles, cousins, brothers, grandfathers, fathers, and stepfathers (Huston, Parra, Prihoda, & Foulds, 1995; Katerndahl, Burge, Kellogg, & Parra, 2005; Romero et al, 1999; Shaw, Lewis, Loeb, Rosado, & Rodriguez, 2001; Ullman & Filipas, 2005). In addition, Romero and colleagues found that four of the women in their study were forced by their families to marry the perpetrators of their abuse.…”
Section: Circumstances Of Abusementioning
confidence: 99%
“…It is consistently reported in the literature that compared to other ethnic groups, Latina women and girls are more likely to be abused by male family members or relatives such as uncles, cousins, brothers, grandfathers, fathers, and stepfathers (Huston, Parra, Prihoda, & Foulds, 1995; Katerndahl, Burge, Kellogg, & Parra, 2005; Romero et al, 1999; Shaw, Lewis, Loeb, Rosado, & Rodriguez, 2001; Ullman & Filipas, 2005). In addition, Romero and colleagues found that four of the women in their study were forced by their families to marry the perpetrators of their abuse.…”
Section: Circumstances Of Abusementioning
confidence: 99%
“…However, African American women were less likely to tell a family member or report it to the police and somewhat more likely to fear negative consequences of disclosing, as compared European American women (Wyatt, 1990b). While comparatively less attention has been paid to the CSA disclosure patterns among Latinas (Ulibarri et al, 2009), some studies suggest that less acculturated Latinas are more likely to report family members as perpetrators and wait comparatively longer to disclose than women from other ethnic groups (Houston et al, 1995; Katerndahl et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Young et al, (2004), for instances, in their study among 25,000 American teenagers found that teenagers who experience external poverty; insufficient family monthly income, impoverished, parents with low educational attainment and performance background, parents employment in low status job and income, and have limited resources are at a greater risk being involved in premature sexual activities and pregnant out of wedlock. Katerndahl et al, (2005) confirmed that a family poverty is the main risk factor for adolescent's premature pregnancy. They studied how the layouts of a crowded home contribute to premature pregnancy among impoverished adolescents.…”
Section: Economically-physically Challenged Family Environmentmentioning
confidence: 65%